DETERMINAN YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus Pada KPP Pratama Jepara) - Istiariani, Irma; Yahya, Imam; Farawansyah , Novita (Universitas Sam Ratulangi, 2026)
Purpose: This research aims to determine the factors of taxpayer compliance, namely taxpayer awareness, level of education, tax sanctions on individual taxpayer compliance at KPP Pratama Jepara. Design/ methodology/ approach: This research uses quantitative methods with a sampling technique, namely simple random sampling. Findings: The results of this research show that taxpayer awareness, level of education, and tax sanctions have a positive and significant effect on the compliance of individual taxpayers registered with KPP Pratama Jepara. Research limitations/ implications: The results of this study are limited to the scope of Jepara Regency only, so they cannot be generalized to other areas. Originality/ value: The combination of three variables of this research are never used in previous research& the used of the grand theory. Key Words : Taxpayer Awareness, Education Level, Tax Sanctions, Taxpayer Compliance.